Synthesis and characterization of CuGaSe2 nanoparticles prepared by a microwave method - S. Tongpeng (2018)
Copper gallium diselenide (CuGaSe 2 ) nanopowder is a p-type semiconductor potentially for use as a thermoelectric material. Nanoparticles of CuGaSe 2 were synthesized by a microwave method using Cu(NO 3 ) 2 • 3H 2 O, Ga 2 (SO 4 ) 3 and SeO 2 as precursors and ethylene glycol as a solvent. A preparative parameter for the synthesis of CuGaSe 2 was a pH value, which varied from 5, 6, 7, 8 to 9. The reaction time in the microwave oven was carried out for 50 seconds; stopped for 3 minutes, 17 cycles at a power of 1100 Watts. From the characterization of product powders by X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques, it was found that CuGaSe 2 powder was successfully synthesized at pH 6. The CuGaSe 2 phase was observed to occur as the main phase with CuSe contaminant. However, the CuSe impurity was decreased when annealed at 560 °C in a nitrogen gas atmosphere for 1 and 3 hours.